On the electrochemical behavior of Cu-16%Zn-6.5%Al alloy containing the β'-phase (martensite) in borate buffer - Blanco, M. [UNESP]; Barragan, J. T C [UNESP]; Barelli, Nilso [UNESP]; Noce, R. D. [UNESP]; Fugivara, Cecilio Sadao [UNESP]; Fernández, J.; Benedetti, Assis Vicente [UNESP] (Elsevier, 2013)
In this work, the electrochemical behavior of Cu-16(wt.%)Zn-6.5(wt.%)Al alloy containing the β'-phase (martensite) was studied in borate buffer solution (pH 8.4) by means of open-circuit potential (EOC), electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The alloy EOC was -0.29 V vs. Hg/HgO/OH-, similar to that of pure copper in this medium, indicating that the processes which occur on the alloy surface are mainly governed by copper. EIS response was related to the dielectric and transmission properties of the complex oxide layer. The CVs showed peaks concerning the redox reactions for copper and zinc. These peaks were assigned to the formation and reduction of copper and zinc species. Furthermore, they showed that the copper oxidation was suppressed by the presence of zinc and aluminum in the alloy composition. The copper and zinc oxidation to form complex oxide layers and the reduction of the different metallic oxides generated in the anodic potential scan suggest that a solid state reaction could determine the metallic oxide formation. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Borate buffer; Cu-Zn-Al alloys; Cyclic voltammetry; Martensite; Alloy compositions; Anodic potentials; Borate buffer solutions; Cu-Zn-Al alloy; Electrochemical behaviors; Open-circuit potential; Transmission property; Aluminum; Aluminum alloys; Anodic oxidation; Copper compounds; Electrochemical impedance spectroscopy; Metals; Oxides; Redox reactions; Solid state reactions; Zinc; Copper